Biomedical Applications of Non-Small Cell Lung Cancer Spheroids - Rozenberg, Julian M.; Filkov, Gleb I.; Trofimenko, Alexander V.; Karpulevich, Evgeny A.; Parshin, Vladimir D.; Royuk, Valery V.; Sekacheva, Marina I.; Durymanov, Mikhail O. (Frontiers in Oncology, 2021)
Lung malignancies accounted for 11 % of cancers worldwide in 2020 and remained the leading cause of cancer deaths. About 80 % of lung cancers belong to non-small cell lung cancer (NSCLC), which is characterized by extremely high clonal and morphological heterogeneity of tumors and development of multidrug resistance. The improvement of current therapeutic strategies includes several directions. First, increasing knowledge in cancer biology results in better understanding of the mechanisms underlying malignant transformation, alterations in signal transduction, and crosstalk between cancer cells and tumor microenvironment including immune cells. In turn, it leads to discovery of important for cancer development molecular targets, which might be affected pharmaceutically. The second direction focuses on the screening of novel drug candidates, synthetic or from natural sources. Finally, “personalization” of therapeutic strategy enables the maximal damage to the patient tumor. The personalization of treatment can be based on the drug screening performed using patient-derived tumor xenografts or in vitro patient-derived cell models. 3D multicellular cancer spheroids, generated from the cancer cell lines or tumor-isolated cells, seem to be a helpful tool for improvement of current NSCLC therapies. Spheroids are used as a tumor-mimicking in vitro model for screening of novel drugs, analysis of intercellular interactions and oncogenic cell signaling. Moreover, several studies with tumor-derived spheroids suggest this model for the choice of “personalized” therapy. Here, we aim to overview different applications of NSCLC spheroids and discuss a potent contribution of the spheroid model to the development of anticancer strategies.